The Middle East in global modernity: Analytic polycentrism, historic entanglements and a rejuvenated area studies debate. Issue 5 (20th October 2021) - Stetter, Stephan
ABSTRACT: I argue that theories of global modernity/world society offer a promising inter-disciplinary approach for theorizing the Middle East. They provide a conceptual umbrella for a rejuvenated Area Studies debate. I turn first to earlier (inter-disciplinary) debates of that kind and then discuss how a rejuvenated debate can reach for new shores: I address the Middle East Area Studies Controversy, and then Fred Halliday's distinction between 'analytic universalism' and 'historic particularism'. Focusing on the interstices between Area Studies and International Relations (IR), I suggest that scholarship on the Arab uprisings offers insights on how to transcend this distinction by shifting to 'analytic polycentrism' and 'historic entanglements'. I identify the unpredictability of power relations and local/global horizons as central, and often marginalized perspectives brought to the fore in post-Arab uprising scholarship. I then discuss how these insights can be linked to innovative (inter-disciplinary) debates in IR that draw from historical-sociological theories of global modernity and world society, especially how the concepts of emergence and evolution as well as differentiation and subjectivity – central pillars of world society theories – can be made of use for the study of the Middle East's place in global modernity and global IR generally speaking.